Restitution of Property Nationalised by the Soviet-style Dictatorships: An Assessment on the Role of the European Court of Human Rights - Veress, Emőd (The ECHR at 70: The Central European Narrative, 2025)
The intersection of the legacies of past totalitarian nationalisations and the current system of human rights protection reveals significant findings. This chapter emphasises the inherent tensions in the human rights framework when dealing with the mass seizure of private property by Soviet-style dictatorships in East Central Europe. This calls for a critical reevaluation of the ability of legal tools to effectively deal with the effects of former totalitarian regimes. The European Court of Human Rights (ECtHR) has approached these challenges with considerable deliberation, fully aware of the substantial and far-reaching implications of its rulings across East Central Europe. However, expecting the Court to resolve the complex issue of equitable restitution for nationalised property, particularly when individual states have struggled and failed to manage it in a fair manner, would be unrealistic. The complexity of this matter has required the ECtHR to adopt a cautious and measured stance, taking into account the broader regional context and the inherent limitations of its mandate. Keywords: nationalisation, restitution, private property, Soviet-style dictatorship, transitional justice